Caracterização morcultural, patogênica e molecular de isolados de Colletotrichum gossypii e Colletotrichum gossypii, var. cephalosporioides - Almeida, Vanessa Cavalcante de (2013)
Considering the importance of identification of Colletotrichum species associated with cotton plants as well as the lack of information about the systematic species, the aim of this work was the realization of characterization morphological and pathogenic of isolates of C. gossypii var. cephalosporioides and C. gossypii subjected to different temperatures, in order to identify possible differences between the two species and evaluate the use of molecular markers for the differentiation of C. gossypii and C. gossypii var. cephalosporioides. Five isolates of C. gossypii var. cephalosporioides and five isolates of C. gossypii were incubated at 20, 25 and 30 °C. Were mensured the mycelial growth, sporulation, the size of conidia as well as topography and color of the colony and the DNA these isolates was used for analysis with molecular markers ERIC-PCR, ISSR, IRAP, REMAP and Box-PCR. Cultural characterization data were subjected to analysis of variance and compared by Tukey test. Pathogenicity data were analyzed employing the Generalized Linear Model. The results revealed that there were differences among the isolates in relation to mycelial growth and sporulation of the two species at different temperatures, no variation in the length and width of conidia was observed. C. gossypii expressed anthracnose symptoms, while symptoms ramulosis were observed only in plants inoculated with C. gossypii var. cephalosporioides. The combination of the five markers amplified 54 loci, of which 48% were polymorphic. The most informative marker was ERIC-PCR. The patterns of DNA bands were used to calculate the values of genetic similarity, which showed minimal similarity of 55% and a maximum of 100%. The dendrogram showed two distinct groups, one including all isolates characterized as C. gossypii and the other group of isolates of C. gossypii var. cephalosporioides indicating that molecular techniques based on the combination of markers ERIC-PCR, ISSR, IRAP, REMAP and Box-PCR were efficient to differentiate C. gossypii of C. gossypii var. cephalosporioides.